Improvement of special physical readiness of the Juvenal category athletes from acrobatic rock'n'roll using functional training tools - Кизім, Петро; Гуменюк, Сергій; Батєєва, Наталія (Slobozhanskyi Herald of Science and Sport, 2018)
Petro Kyzim, Serhii Humeniuk & Nataliya Batieieva Purpose: to develop and experimentally substantiate the method of improving the special physical readiness of the athletes of the Juvenile category with acrobatic rock'n'roll using the means of functional training. Material & Methods: theoretical analysis and generalization of data from special scientific and methodological literature, pedagogical observation, pedagogical testing, pedagogical experiment, methods of mathematical statistics. The survey involved 40 athletes (20 sports pairs of the Juvenaly category). Results: the use of the means of functional training of the experimental technique has improved the level of special physical readiness of athletes. Conclusion: the positive effect of the means of functional training in the components of speed, power and speed-strength training on the dynamics of the level of special physical readiness of athletes from acrobatic rock'n'roll.